Comparação da dor pós-operatória em cães versus gatos após orquiectomia versus ovariohisterectomia - Quarterone, Carolina [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Veterinarians attribute a higher pain scores and give more analgesics to dogs compared to cats. Both female dogs and cats receive more analgesia than males for the same surgical procedures. This study aimed to compare the expression of pain after orquiectomy and ovariohisterectomy of the same species and between the canine and feline species undergoing contraceptive surgery. Cats (24) and dogs (24) were enrolled in the study, with the same number of males and females. The animals were admitted 24 hours prior to the study for adaptation to the hospital environment and the observer. Meloxicam (0.1 mg/kg P.O.) was administered two hours before the surgical procedure. Pain scales were applied before (basal) and 1, 2, 4, 8 and 24 hours after surgery (M1, M2, M4, M8 and M24 respectively). Glasgow Composite Measure Pain Scale (GCMS) and Melbourne pain scale (MPS) were used in dogs, and UNESP-Botucatu Multidimensional Composite Pain Scale (UBMCP) in cats. When the score was above 33% for GCMS or 27% for MPS, analgesic rescue was given (morphine, 0.5 mg/kg for dogs and 0.3 mg/kg for cats). In both species the visual analogue pain scale (VAS) and sedation were recorded. Mann-Whitney was used to compare data between male and female (P < 0.05). Kruskall-Wallis was used to compare differences among groups, followed by Dunn test (P < 0.05). Friedman test compared differences along time (P < 0.05). When compared to baseline female dogs and cats had greater VAS from 1 to 4 h, male dogs and cats from 1 to 8 h and from 1 to 2 h after surgery, respectively. VAS values were higher in female dogs from 1 to 8 h than in male ones, and in female cats this value were higher at 4 h, compared to male cats. In GCMS, scores were greater compared to baseline for females between 1 and 4 h after surgery and at 1 h compared to males. There was no difference for MPS. For UBMCP, greater scores were observed in females compared to males between 1 and 2 h and at 2 h ...

Historicamente os profissionais veterinários atribuem escores mais altos de dor e maior emprego de analgésicos na espécie canina em relação à felina e fêmeas em relação aos machos. O objetivo deste foi comparar a expressão da dor entre orquiectomia e ovariohisterectomia na mesma espécie e entre as espécies canina e felina submetidos à cirurgia contraceptiva. Utilizaram-se 48 animais, 12 machos e 12 fêmeas da espécie felina de raças variadas, com idade média 12 ± 4,32 e 8 ± 2,54 meses e massa corpórea de 3,9 ± 0,96 e 2,58 ± 0, 41 kg respectivamente, e 12 machos e 12 fêmeas da espécie canina, de raças variadas, com idade média de 20,8 ± 13,7 e 44 ± 23,6 meses e massa corpórea 20,3 ± 12,2 e 14,8 ± 8,6 kg respectivamente. Administrou-se meloxicam 0,1 mg/kg via oral (VO) duas horas antes do procedimento. Avaliou-se a dor antes (basal) e 1, 2, 4, 8 e 24 horas após a cirurgia. Para determinar os escores de dor em cães utilizou-se a Escala de Dor de Glasgow Modificada (EDGM) e da Universidade de Melbourne (EDUM). Para os gatos empregou-se a Escala de Dor Multidimensional da Unesp-Botucatu (EDMUB). Utilizaram-se a escala analógica visual para dor (EAV) e escala de sedação em ambas as espécies. Quando a pontuação era maior que 33% e 27% do valor total da EDGM e EDMUB respectivamente, realizava-se resgate analgésico com morfina. Como as variáveis não apresentaram distribuição normal, empregou-se o teste de Friedman e Mann-Whitney, para comparar as diferenças ao longo do tempo e entre os grupos em cada momento, respectivamente. Para comparação entre mais de dois grupos, utilizou-se o teste Kruskall-Wallis, seguido do teste de Dunn. Para diferenças de frequência de resgates analgésicos entre os grupos utilizou-se o teste exato de Fisher. Consideraram-se as diferenças significantes quando P < 0,05. As fêmeas de ambas as espécies apresentaram aumento da EAV de 1 a 4 h, os cães de 1 a 8 h e os gatos de ...
Keywords: Cão - Cirurgia; Gato - Cirurgia; Analgesia; Dor pos-operatoria; Analgesicos; Orquiectomia; Histerectomia; Postoperative pain